Postural and Intention Tremors: A Detailed Clinical Study of Essential Tremor vs. Parkinson’s Disease - Sternberg, Eliezer J.; Alcalay, Roy N.; Levy, Oren A.; Louis, Elan D. (Frontiers in Neurology, 2013)
ABSTRACT Background: An estimated 30-50% of essential tremor diagnoses are incorrect, and the true diagnosis in those patients is often Parkinson’s disease or other tremor disorders. There are general statements about the tremor in these essential tremor and Parkinson’s disease, but published data on the more subtle characteristics of tremor are surprisingly limited. Postural tremor may occur in both disorders, adding to the difficulty. There are several anecdotal impressions regarding specific features of postural tremor in essential tremor vs. Parkinson’s disease, including joint distribution (e.g., phalanges, metacarpal-phalangeal joints, wrist), tremor directionality (e.g., flexion-extension vs. pronation-supination), and presence of intention tremor. However, there is little data to support these impressions. Methods: In this cross-sectional study, 100 patients (essential tremor, 50 Parkinson’s disease) underwent detailed videotaped neurological examinations. Arm tremor was rated by a movement disorder neurologist who assessed severity and directionality across multiple joints. Results: During sustained arm extension, essential tremor patients exhibited more wrist than metacarpal-phalangeal and phalangeal joint tremor than did Parkinson’s disease patients (p<0.001), and more wrist flexion-extension tremor than wrist pronation-supination tremor (p<0.001). During the finger-nose-finger maneuver, intention tremor was present in approximately one in four (28%) essential tremor patients vs. virtually none (4%) of the Parkinson’s patients (p<0.001). Conclusions: We evaluated the location, severity, and directionality of postural tremor in essential tremor and Parkinson’s disease, and the presence of intention tremor, observing several clinical differences. We hope that detailed phenomenological data on tremor in essential tremor and Parkinson’s disease will help practicing physicians delineate the two diseases.